Kecukupan Gizi Pada Rentang 1000 Hari Pertama Kehidupan Sebagai Upaya Penanggulangan Dan Pencegahan Stunting Di Desa Tenggela, Gorontalo - Zul Fikar Ahmad; Siti Surya Indah Nurdin; Ardiansyah Ardiansyah (Universitas Negeri Makassar, 2022)
Eating a nutritious diet is an important behavior for a child's health and development. The first 1000 days of life are an important period in the growth and development of children, where the disorders that arise during this period will have permanent and irreversible consequences. This service aims to increase knowledge about nutritional adequacy in the range of 1000 HPK. The service in the Tenggela Village office hall, Tenggela Village, the working area of the Tilango Health Center, Gorontalo Regency. The service is carried out in the form of counseling with the dedication method using lectures with the help of Power Point and discussions with participants. The participants of the activity were the Tenggela Posyandu participants. The implementation of activities is self-funded by the executor. This service activity can be carried out well and can achieve the expected goals of the implementer. In the future, further service activities can be carried out in a sustainable manner either in the same place or in other places